Recent Advances in Cross-Couplings of Functionalized Organozinc Reagents - Wei, Baosheng; Knochel, Paul (Synthesis, 2021)
Cross-couplings involving organozinc reagents usually require a Pd-catalyst (Negishi cross-coupling), however, uncatalyzed cross-couplings of zinc organometallics proceed well in the absence of transition-metal catalysts with reactive electrophiles such as benzal 1,1-diacetates, benzhydryl acetates, and iminium trifluoroacetates. Organozinc compounds also undergo C–N bond formation with O-benzoylhydroxylamines or organic azides in the presence of cobalt- or iron-catalysts. Highly diastereoselective and enantioselective cross-couplings can be readily performed with room-temperature configurationally stable alkylzinc species, producing diastereoselectively and enantiomerically enriched products. Finally, highly regioselective magnesiations of functionalized arenes and heteroarenes undergo Negishi (after transmetalation with ZnCl2) or Cu-catalyzed cross-couplings.1 Introduction2 Uncatalyzed Cross-Couplings of Organozinc Reagents with Highly Electrophilic Partners3 Iron- and Cobalt-Catalyzed Aminations using Organozinc Reagents4 Stereo- and Regioselective Cross-Couplings of Organozinc Reagents5 Conclusion
Keywords: cross-coupling; organozinc reagents; carbon–carbon bond formation; carbon–nitrogen bond formation; amination; diastereoselective reaction; enantioselective reaction